Regulator rozmyty jako przykład algorytmu odpornego - Pauluk, Mariusz (Wydawnictwa AGH, 2006)
The paper presents a fuzzy controller, that controls a three dimensional laboratory crane model in real time. Some basic definitions, which the construction of the controller is based on, were also brought up. The control process is noise robust. Basing on received experimental results, likewise on graphic analyze of the control set, an influence of the separate fuzzy rules on quality of the process control was showed. The experiments were carrying up in the MATLAB-Simulink software environment.

W pracy przedstawiono regulator rozmyty sterujący w czasie rzeczywistym modelem laboratoryjnym suwnicy trójwymiarowej. Przytoczono także podstawowe definicje, na których podstawie skonstruowano regulator. Regulacja odbywa się w sposób odporny na zakłócenia. Na podstawie otrzymanych rezultatów eksperymentalnych, jak również poprzez analizę graficznej reprezentacji sterowania, pokazano wpływ poszczególnych reguł na jakość sterowania. Eksperymenty przeprowadzono w pakiecie MATLAB-Simulink
Fuzzy controller as the example of the robust algorithm
Automatyka
Keywords: fuzzy controller; robust control; regulator rozmyty; sterowanie odporne; 3D crane; suwnica 3D